Editorial for Special Issue “Reclaiming Voices: Women’s Contributions to Baptist History” - Melody Maxwell (Religions)
Women make up more than half of Baptist church members globally, yet many histories of Baptists have neglected women, focusing instead on men and the institutions they lead [...]